VULVODYNIA AS A CHRONIC VULVAR PAIN DISORDER: A NARRATIVE REVIEW OF PATHOPHYSIOLOGY, DIAGNOSIS, AND MANAGEMENT - Dobrowolska, Agnieszka; Skrobarczyk, Adam; Drewniak, Zuzanna; Rząsa, Marta; Rycman, Karolina; Sternik, Martyna; Wendrychowicz, Kamil; Wróbel, Filip (International Journal of Innovative Technologies in Social Science, 2026)
Background: Vulvodynia is a chronic vulvar pain condition frequently associated with dyspareunia and significant impairment of quality of life in women of all ages. Despite increasing clinical awareness, diagnosis and management remain challenging due to its heterogeneous presentation and multifactorial etiology. Aim: This review aims to evaluate the current understanding of the pathogenesis, clinical presentation, diagnostic approaches, and management strategies of vulvodynia, and to synthesize available evidence to support clinical practice and guide future research. Methods: A narrative review of the literature was conducted using PubMed, Scopus, Web of Science, and Embase, focusing on publications from 2005–2025. Additional sources included reference screening and international society guidelines. Narrative and systematic reviews, meta-analyses, consensus statements, clinical guidelines, and relevant observational or experimental studies were included. Due to methodological heterogeneity, findings were synthesized narratively. Results: According to the International Society for the Study of Vulvovaginal Disease, vulvodynia is defined as vulvar pain lasting at least three months without an identifiable cause. Current evidence suggests a multifactorial pathophysiology involving neurogenic, inflammatory, myofascial, hormonal, and psychosocial mechanisms, including central sensitization. Diagnosis relies on detailed history-taking, comprehensive physical examination, targeted pain assessment, and exclusion of other gynecologic, dermatologic, or neurologic conditions. Management increasingly emphasizes a multimodal, interdisciplinary approach combining patient education, pelvic floor physical therapy, psychological interventions, and pharmacological treatment. Conclusions: Vulvodynia is a complex chronic pain disorder requiring individualized, patient-centered care. Interdisciplinary management tailored to underlying pain mechanisms and coexisting factors is essential to improve clinical outcomes and quality of life.